Presence of Chlamydia suis and Chlamydia abortus in Pigs from Mexico; first report - Hernández-Ramírez, Paola-Alexis; María-Magdalena, María-Magdalena; Pérez-Romero, Nelson; Palomares-Resendiz, Gabriela; Hernández-Castro, Rigoberto; Díaz-Aparicio, Efrén; Arellano-Reynoso, Beatriz (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: The genus Chlamydia comprises obligate intracellular Gram-negative bacteria responsible for various diseases in animals and humans. In pigs, the species C. suis is transmitted via aerogenic, genital, and oral routes, with its pathogenicity associated with conjunctival tissue, the respiratory system, the gastrointestinal tract, and the reproductive system. In addition to C. suis, other Chlamydia species have been identified in pigs. In Mexico, chlamydiosis was considered an exotic disease until 2016, the year it was recognized as endemic in birds and ruminants; however, there are no reports of this disease in pigs. Objective: This study aimed to detect the presence of Chlamydia suis and Chlamydia abortus in sows that had experienced abortion and conjunctivitis. Methods: This study examined the presence of Chlamydia suis and Chlamydia abortus in pigs from four farms in central Mexico between 2016 and 2022, focusing on animals exhibiting reproductive issues, conjunctivitis, or diarrhoea. A total of 141 samples, including vaginal exudates (122), conjunctival exudates (17), and faeces (2), were analysed using real-time PCR (qPCR) to detect Chlamydiaceae and specific Chlamydia species. Results: The results revealed that 40.42% of samples tested positive for Chlamydiaceae. Among these, 43.85% were positive for C. abortus and 24.56% for C. suis, with 13 samples showing co-infection. Neither C. pecorum nor C. psittaci were detected. Furthermore, 54.4% of positive samples could not be identified at the species level, highlighting the necessity for further genomic analysis. Conclusions: These results align with global reports on Chlamydia prevalence in pigs and underscored the significance of co-infections, which were observed in vaginal exudates, faeces, and conjunctival samples. This study constituted the first report of porcine chlamydiosis in Mexico, raising concerns about potential health risks for pig farms and zoonotic implications for humans. The study emphasized the need for improved surveillance of Chlamydia species across production stages and advocates further research into the genetic diversity and prevalence of Chlamydia in Mexico.